Laicidade na relação igreja-estado e o acordo Brasil - Santa Sé - Alberton, Genacéia da Silva (2012)
In the relationship between Church and State, laicity is the tensioning element that maintains the autonomy between religious and public life. While it should not be confused with laicism, laicity is one of the characteristic aspects of secularization with laicism taking on an air of anti-clericalism. Through the conciliar documents Lumen Gentium and Gaudium et Spes, the Second Vatican Council responded to the signs of the times. While reaffirming the primacy of the Church, the Council recognized religious freedom as a right that is integral to human dignity and that must be preserved. The Church as communion and participation has given the laity greater scope for action which surpasses their responsibility as mere cooperating agents in liturgical acts and makes them effective protagonists in the century. As a result, Christian action in the public space of the State arises as an exercise of rights in the face of religious pluralism, and religious freedom becomes a fundamental right. Public reason shall be the basis of the argument that human dignity and protection of fundamental rights are the axes permitting cooperation between Church and State in the search for the common good, with respect for the autonomy of each institution in its own sphere. The Agreement between Brazil and the Holy See is the document that gives vigor to the harmonious relationship between the Catholic Church and the Brazilian State in a lay country in which the democracy strengthened by the Constitution of 1988 gives rise to questions regarding religion in the public space. The Agreement, in the framework of the Church's policy of action, solidifies the positions secured by jurisprudence, makes it possible to guarantee the Church's free action in its mission, and gives rise to the use of public reason to guarantee fundamental rights and religious freedom in the face of legal demands. The tensions resulting from laicism require the Church to develop its ability to listen and dialogue. They also require the Brazilian State to recognize the cultural and religious importance of the Catholic Church, overcoming conflicts in spaces other than the judiciary, and strengthening a healthy laicity and cooperation for the common good